analisis pembelajaran tematik pada muatan IPS saat BDR (Belajara Dari Rumah) di Kelas V Sekolah Dasar Kota Bengkulu - Gusti Permata Sari Sari; Badeni; Puspa Djuwita (UNIB Press, 2022)
This study aims to: (1) describe the teacher's process in planning thematic learning on social studies content during BDR (Learning From Home) during the covid-19 pandemic in class V of Bengkulu City Elementary School; (2) Describe the teacher's process in carrying out thematic learning on social studies content during BDR (Learning From Home) during the covid-19 pandemic in class V of Bengkulu City Elementary School; (3) Describe the teacher's process in evaluating thematic learning on social studies content during BDR (Learning From Home) during the COVID-19 pandemic in class V of Bengkulu City Elementary School. This type of qualitative descriptive research by analyzing the data collected in the form of wordsP, pictures and not numbers to get an objective description. The research subjects in this study were 5th grade teachers who taught at SD Negeri 53, SD Islam Al-Azhar and SD Negeri 29 Bengkulu City, parents of students. The collection procedure carried out by researchers by conducting interviews, and documentation. Data Analysis Techniques in this research by reducing data, displaying data and verifying data based on the research results obtained. The results of the study found that the Management of Thematic Learning on Social Studies Content While Studying from Home (BDR) in class V of Bengkulu City Elementary School, the teacher had made maximum efforts when faced with the current covid 19 pandemic condition by starting from designing learning plans that were made according to conditions. , the implementation of learning is carried out in accordance with the current situation and condition of students so that learning objectives are achieved and conduct an assessment / evaluation of learning seen from the cognitive aspect only because when they want to assess affective and psychomotor aspects, they are constrained by pandemic conditions so that teachers cannot make direct observations of students only. carry out an assessment in the form of a written test that is sent via the WhatsApp group only. From this condition, the teacher must be smart in managing the class so that learning can run according to the expected learning objectives.